Selected phytochemicals of Momordica charantia L. as potential anti-DENV-2 through the docking, DFT and molecular dynamic simulation - Huq, A. K. M. Moyeenul; Roney, Miah; Issahaku, Abdul Rashid; Suhaila, Sapari; Fazira Ilyana, Abdul Razak; Soliman, Mahmoud E. S.; Mohd Fadhlizil Fasihi, Mohd Aluwi; Saiful Nizam, Tajuddin (Taylor & Francis, 2023)
Dengue fever is now one of the major global health concerns particularly for tropical and sub-tropical countries. However, there has been no FDA approved medication to treat dengue fever. Researchers are looking into DENV NS5 RdRp protease as a potential therapeutic target for discovering effective anti-dengue agents. The aim of this study to discover dengue virus inhibitor from a set of five compounds from Momordica charantia L. using a series of in-silico approaches. The compounds were docked into the active area of the DENV-2 NS5 RdRp protease to obtain the hit compounds. The successful compounds underwent additional testing for a study on drug-likeness similarity. Our study obtained Momordicoside-I as a lead compound which was further exposed to the Cytochrome P450 (CYP450) toxicity analysis to determine the toxicity based on docking scores and drug-likeness studies. Moreover, DFT studies were carried out to calculate the thermodynamic, molecular orbital and electrostatic potential properties for the lead compound. Moreover, the lead compound was next subjected to molecular dynamic simulation for 200 ns in order to confirm the stability of the docked complex and the binding posture discovered during docking experiment. Overall, the lead compound has demonstrated good medication like qualities, non-toxicity, and significant binding affinity towards the DENV-2 RdRp enzyme.